Detection of Jumps Parameters in Economic Processes(the Case of Modelling Profitability) - V. Poliarus, O.; O. Poliakov, Y.; L. Nazarenko, I.; T. Borovyk, Y.; V. Kondratiuk, M. (International Journal of Engineering and Technology, 2018)
A new method of parameters jumps detection in economic processes is presented. A jump of the economic process parameter must be understood as a rapid parameter change for a time that does not exceed the period of process registration.Â  A system of stochastic differential equations for a posteriori density probability of a jump is synthesized. The solution of the system is the probability of a parameter jump, the estimation and variance of the jump in the presence of a priori information under conditions of noise influence. The simulation results are conducted for profitability of machine building industry of Kharkiv region, Ukraine. The system provides detection of jump parameters, even in conditions of intense noise of economic nature. To increase the probability of finding jumps it is necessary to have a priori information.Â Â